Composite amplitude-shift keying for effective LED-camera VLC - Yang, Y. (2021)
LED-Camera Visible Light Communication (VLC) is gaining increasing attention, thanks to its readiness to be implemented with Commercial Off-The-Shelf devices and its potential to deliver pervasive data services indoors. Nevertheless, existing LED-Camera VLC systems employ mainly low-order modulations such as On-Off Keying (OOK) given the simplicity of their implementation, yet such rudimentary modulations cannot yield a high throughput. In this paper, we investigate various opportunities of using a high-order modulation to boost the throughput of LED-Camera VLC systems, and we decide that Amplitude-Shift Keying (ASK) is the most suitable scheme given the limited operating frequency of such systems. However, directly driving an LED to emit different levels of luminance may suffer heavy distortions caused by the nonlinear behavior of LED. As a result, we innovatively propose to generate ASK using the composition of light emission. In other words, we digitally control the On-Off states of several groups of LED chips, so that their light emissions compose in the air to produce various ASK symbols. We build a prototype of this novel ASK-based VLC system and demonstrate its superior performance over existing systems: it achieves a rate of 2 kbps at a 1 m distance with only a single LED luminaire for static users and more than 1 kbps for mobile users.